A 3D Empirical Model of Electron Density Based on CSES Radio Occultation Measurements. Issue 5 (22nd May 2022) - Huang, He; Lin, Jian; Xu, Song; Le, Huijun; Guo, Feng; Zeren, Zhima; Liu, Libo; Shen, Xuhui
Abstract: China Seismo‐Electromagnetic Satellite (CSES) was successfully launched in February 2018. About 280 thousand ionospheric radio occultation (RO) electron density profiles (EDP) have been accumulated till the end of 2020. The CSES is a Sun‐synchronous orbit satellite with descending and ascending nodes around 14:00 and 02:00 LT, respectively, at the height of 507 km. Thus, most of the RO EDP concentrate on these two local time bins. First, we constructed empirical NmF2, hmF2, and Hm models at two local time windows 14:00 and 02:00 LT, respectively. The three models describe that NmF2, hmF2, and Hm vary with solar activity, season, longitude, and latitude. Through the comparison with CSES observations, the NmF2, hmF2, and Hm models could reproduce the physical characteristics rather well. Then, according to Chapman profile function, a EDP model was reconstructed based on the NmF2, hmF2, and Hm models, named CSES_Ne‐Profile Model. To evaluate the model performance, we simulated the COSMIC‐2 observations by CSES_Ne‐Profile Model and international reference ionosphere (IRI) model respectively. The results show that CSES_Ne‐Profile Model precedes the IRI model. Additionally, our model captures the merging phenomenon of the two peaks of equatorial ionospheric anomaly, which is missed by IRI. Further, CSES_NePrf model is a useful tool to provide the quiet background for case studies and joint studies with other payloads onboard CSES. Plain Language Summary: China Seismo‐Electromagnetic Satellite (CSES) was successfully launched in February 2018. The onboard occultation receivers receive signals from global navigation satellite system, which can be used to retrive electron density profiles (EDP). The CSES is a Sun‐synchronous orbit satellite at the height of 507 km. For this reason, most of the EDP concentrate on 14:00 and 02:00 LT. First, we constructed empirical models for three parameters at two local time window 14:00 and 02:00 LT, respectively. Solar activity, season, longitude, and latitude variations for the three parameters are well presented by the models. Through the comparison with CSES observations, the three models capture the physical characteristics rather well. Then, a EDP model was constructed based on these three models according to Chapman profile, named CSES_Ne‐Profile Model. The model performance is evaluated by reproducing the COSMIC‐2 observations by CSES_Ne‐Profile Model and international reference ionosphere (IRI) model respectively. The results show that CSES_Ne‐Profile Model is in the lead of the IRI model. Additionally, our model capture the some feature, which is missed by IRI. Further, CSES_NePrf model is a useful tool to provide the quiet background for case study and joint study with other payloads onboard CSES. Key Points: The first 3‐D empirical electron density model was constructed based on CSES‐01 radio occultation observations The model reproduces the COSMIC‐2 observations very well, overmatching the international reference ionosphere model The model provides the quiet background for case study and joint study with other payloads onboard CSES‐01